2011
DOI: 10.1038/jhh.2011.41
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anthocyanins on blood pressure and stress reactivity: a double-blind randomized placebo-controlled crossover study

Abstract: High intakes of flavonoids are associated with reduced cardiovascular risk, and flavonoids such as cocoa and soy protein isolate have shown beneficial effects on blood pressure (BP). Anthocyanins constitute a flavonoid subgroup consumed in regular diets, but few studies have assessed the antihypertensive potential of anthocyanins. We aimed to assess whether high concentrations of relatively pure anthocyanins reduce BP and alter cardiovascular and catecholamine reactivity to stress. A total of 31 healthy men be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 26 publications
2
38
1
2
Order By: Relevance
“…Furthermore, meta-analysis data have indicated that FMD increases linearly to a consumption of #500 mg total cocoa polyphenols, after which a decrease in the percentage of FMD was observed at higher intakes (43), and dose-response relations were nonlinear between FMD and flavonoid dose (44). No changes in secondary markers of vascular function were observed at any of the time points or intakes used, which agreed with data that indicated that PWV (20) and blood pressure (18,45) are not acutely altered after flavonoid interventions.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, meta-analysis data have indicated that FMD increases linearly to a consumption of #500 mg total cocoa polyphenols, after which a decrease in the percentage of FMD was observed at higher intakes (43), and dose-response relations were nonlinear between FMD and flavonoid dose (44). No changes in secondary markers of vascular function were observed at any of the time points or intakes used, which agreed with data that indicated that PWV (20) and blood pressure (18,45) are not acutely altered after flavonoid interventions.…”
Section: Discussionsupporting
confidence: 77%
“…The rationale for this allowance was that if participants were still having high blood pressure despite the intake of pharmaceuticals, they could benefit from the intake of the current study product. In a randomised double-blind crossover study, a 4-week intake of a high level of anthocyanins, extracted from bilberries and black currants, did not lower the blood pressure (screening BP >140/90 mmHg) of otherwise healthy people (Hassellund, Flaa, Sandvik, Kjeldsen, & Rostrup, 2012). The inconsistent findings regarding the antihypertensive potential of blueberries could be due to variations among different blueberry species, the amount consumed and the presence of different active compounds in whole blueberries other than pure anthocyanins.…”
Section: Discussionmentioning
confidence: 95%
“…A decrease in BP has been reported after chronic intakes (6-8 weeks) of mixed berries, anthocyaninrich tea, and chokeberry and blueberry extracts by hypertensive individuals, myocardial infarction survivors, and those with markers of the metabolic syndrome (27,132,300,331,345). In contrast, a similar number of studies have reported a lack of efficacy of chronic intake of anthocyanin-rich foods, such as blueberry and cranberry juice in healthy individuals, chronic smokers, people with dyslipidemia, obese subjects, stage 1 hypertensive individuals, and CAD patients (114,115,182,297,366,448). Similarly, grapes and grape seed extract have also been shown not to influence BP in healthy or diseased individuals (302,472,488,509).…”
Section: Berriesmentioning
confidence: 99%